Indofood in Global Market: The Dialectics of International Investment Law and Horizontal Production Strategies - Dahayu Firda Auliya; Hana Solehah Nadia (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The growing internationalization of emerging-market multinational enterprises has generated increasing scholarly interest in the relationship between corporate expansion strategies and international investment governance. This study examines the dialectical interaction between International Investment Law (IIL) and horizontal production strategies through the case of PT Indofood CBP Sukses Makmur Tbk’s global expansion, particularly following its acquisition-driven internationalization into Africa and the Middle East. Employing a non-empirical qualitative design grounded in a normative-conceptual approach, the research integrates horizontal Foreign Direct Investment (FDI) theory, the proximity–concentration trade-off paradigm, and contemporary developments in international investment law. The analysis relies on doctrinal legal interpretation, corporate documentation, policy materials, and relevant academic literature to evaluate how legal frameworks and production-location decisions mutually shape multinational competitiveness. The findings indicate that horizontal production strategies enhance market responsiveness, operational flexibility, and product adaptation, while international investment law provides legal certainty, investment protection, and institutional stability necessary for cross-border business operations. The study further demonstrates that sustainable global competitiveness is achieved through the alignment of production localization, regulatory adaptation, and investment governance. The research contributes to the literature by offering an integrated analytical framework linking international economics, strategic management, and international investment law in explaining outward FDI from emerging-market firms.